Curcumin as a Supportive Therapy in Type 2 Diabetic Patients - Anand Seth; Sravya Iyyuni; Saurabh Sharma; Ritu Sethi; Suresh Nath; Michael Imeokparia (Advances in Public Health)
Type 2 diabetes mellitus (T2DM) is a growing public health concern. The management of diabetes is a lifelong process that requires diabetic education, attempts to achieve near optimal glycemic control, minimizing cardiovascular and other long-term risk factors, and avoidance of drugs that can exacerbate abnormalities of insulin and lipid metabolism. In the treatment of T2DM, curcumin has demonstrated much potential as an adjunct therapy due to its anti-inflammatory properties and its ability to reduce oxidative stresses within the body. However, the low bioavailability poses limitations to its therapeutic potential. In this paper, we discuss the benefits of curcumin in a healthy diet, its potential and limitations as a supportive therapy. The Ayurvedic perspective of curcumin in diabetes is also discussed. Mechanisms for increasing the bioavailability of the supplement is discussed. Also, epigenetic regulation of type 2 diabetes is discussed, especially the role of DNA methylation.